(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This paper aims at presenting some results obtained in an extension project developed within a public institution in the region known as “Alto Vale do Itajaí”, in Santa Catarina. The extension project entitled “Basic English Course for Seniors” aimed at offering English language classes to groups over 55 years old in a region marked by German colonization, that is why it might be considered a complex sociolinguistic scenario. Our discussion is based on field data collected during the activities of the project. Learning a new language, besides being a challenging experience, offers the discovery of new resources and skills and it reveals itself as a stimulus to the learner. The analyzed data indicates the motivations for instrumental and integrative orientation of the participants. Through the interaction among the participants in the classes it was possible to observe that life experiences, especially childhood memories, stand out in their conversation in class. Thus, it might be assumed that the students’ conception and beliefs that personal experiences are part of the language learning process become evident. It is assumed that learning a foreign language will contribute for the elderly to remain socially active, in addition to providing contact with new cultures and new individuals.